Fatal exit : - Kowalick, Tom (Wiley, 2005)
FATAL EXIT is the first and only book documenting the decades-long debate among the automotive industry, government regualtors, and safety and privacy advocates over what the public terms "automobile black boxes". The book briefly traces the history of the debate from 1974 to 2004, and then clearly presents opposing viewpoints for and against the widespread use of emerging Motor Vehicle Event Data Recorder (MVEDR) technology.